A Right to Be Lazy? Busyness in Retrospective. - Cross, Gary (Social Research)
Part of a special issue on busyness. The writer reviews the history of work time and leisure. Many people in the late 19th century, including Marx's son-in-law Paul Lafargue, believed that busyness was a false doctrine of modern capitalism and that overwork caused production gluts and the irrational excesses of the rich. However, strong cultural, technological, political, and even biological forces have since combined to not only make people busy but to make the virtues and rights of “laziness” unintelligible. There are many short-term benefits from the busyness culture and many long-term barriers to making other choices, but the truth is that the personal costs of busyness are huge, namely the long-term loss of health and social relationships.